Pengaruh Kesadaran Wajib Pajak, Sanksi, dan Pemutihan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi pada Badan Pendapatan Daerah Provinsi Sumatera Selatan) - Aji Pranata; Nurmala Nurmala; M. Aryo Arifin (Universitas Kristen Maranatha, 2022)
This study aims to test the hypothesis of the effect of taxpayer awareness, tax sanctions, andtax whitening, on motor vehicle taxpayer compliance at the South Sumatra Regional RevenueAgency for the period 2018-2021. The data used is by distributing questionnaires. Thepopulation in this study was 33,130 motor vehicle taxpayers in the city of Palembang whowere registered with the Regional Revenue Agency of South Sumatera Province. In this study,the authors used a sample of 100 respondents/taxpayers using the slovin formula. Methods ofdata collection using primary and secondary data. The analytical technique used in thisstudy is multiple linear regression with the help of SPSS 22.0 software for windows. Theresults of the hypothesis test conclude that the taxpayer awareness variable significantlyaffects the compliance of motorized vehicle taxpayers by 0.00 <0.05, the tax sanctionsvariable has an effect on significant effect on motor vehicle taxpayer compliance by 0.00< 0.05, and the variable tax whitening has an effect on motor vehicle taxpayer compliance by0.01 < 0.05 at the Regional Revenue Agency of South Sumatra Province in 2018-2021.Keywords: Taxpayer Awareness, Tax